Occupational profile and prevalence of workplace accidents among beach workers - Cleber Cremonese; Adedayo Michael Awoniyi; Mariela Sousa dos Santos; Jailma dos Santos Silva; Thayane Silva Nunes; Wiler de Paula Dias; Joelma Marques Rodrigues; Juliana Cristina dos Santos Soares; Armando Meyer (PLoS ONE, 2025)
Background Workplace accidents (WAs) are acute, often preventable events that result in injuries or functional impairments, typically arising from occupation-related activities. In 2019, an estimated 395 million workers worldwide suffered non-fatal work-related injuries, with 330,000 fatalities, the majority occurring in low- and middle-income countries (LMICs) like Brazil. The true figures may be considerably higher due to underreporting, as many informal workers lack adequate social protection and may avoid reporting accidents for fear of jeopardizing their livelihood. Objective To assess the prevalence of WAs and their association with demographic and occupational determinants among beach workers in Salvador, Bahia, Brazil, between 2023 and 2024. Methods A cross-sectional epidemiological study was conducted with 579 urban beach workers in Salvador from November 2023 to March 2024. Following ethical approval and participants’ consent, questionnaires were administered to gather data on sociodemographic and occupational characteristics, workplace environments and processes, workplace-related injuries and illnesses, and history and characteristics of WA. WA prevalence and prevalence ratios were calculated, and associations were analyzed using a Poisson regression model with robust variance. Results Among the workers, 59.4% were males, 25% were aged ≤29 years and 11.4% were ≥60 years. Black and brown individuals represented 92.9% of the population. The most performed activities were street vendors (43.6%) and waiters (25%). Informal employment was reported by 72.3% of workers, 70.2% worked ≥9 hours per day, and 88% had no occupational training. The overall WA prevalence observed was 40.3%, with workers ≤29 years old having a 2.59 times higher likelihood of experiencing WA compared to those ≥60 years old. The most common WAs were punctures (42.7%), cuts (28.4%) and burns (12.1%). Conclusions The high prevalence of WA among beach workers, especially those ≤29 years old, may be associated with inadequate working conditions, including long working hours and lack of occupational training. These findings highlight the need for targeted interventions to improve working conditions and reduce WA risks.